Mulheres negras da montanha: a religiosidade das benzedeiras de Rio de Contas - Aguiar, Gilberto Orácio de (2012)
When writing this passage about black women and female healers from the mountains of Rio de Contas BA, we will discuss about benediction, perhaps, in a way never studied before. Our research is carried out on a tripod that presents itself as axles - chapters that seek to answer to the relationship of black female healers of Rio de Contas, of their foremothers through the orality. To realize this endeavor, we will observe certain approaches, such as the history of the city of Rio de Contas with its natural, social and religious aspects, from historical texts and supplies of Municipal Historic Archives; about the black women history in Brazil and its direct relationship with the African women, mainly regarding to religiosity, commercial art and their collaboration in the development of a national identity; about the benediction as a split of act of caring and their 'risks' for women, especially in Middle Ages when they were chased as disseminators of devil actions. All this supported by interviews that will emphasize to the characterization of benediction in Rio de Contas with material respects. Life is woven in the comings and goings of everyday life, thereby producing balance and unbalance. The benediction, as an aspect of popular religiosity, presents itself as an effective symbolic way on the reelaboration of lost possibilities in articulation of citizenship. Through the orality and memory reconquered on the prayers and gestures of healing we find in each black Rio das Contas benedict, an alternative capable of realign human being willing to be good to accomplish your task in the world where is located. Each of these female healers carries the 'gift' of being a woman, black, mother, aunt, grandmother, godmother, midwife, with its social consequences. It is a positive reference amid the wreckage of a competitive society that still seeks for the transcendent through the magic ways